The Shell Motif in the Culture and Architecture of the Ancient Town of Marina el-Alamein in Egypt - Bąkowska-Czerner, Grażyna; Czerner, Rafał (Études et Travaux, 2021)
At the archaeological site of Marina el-Alamein in Egypt, many monuments and everyday objects feature motifs related to Aphrodite and her cult. One recurring theme is the seashell that lamps are often decorated with. In one case, it accompanies the depiction of the goddess herself. This article collects oil lamps with the image of a scallop shell from the research of the Polish-Egyptian Conservation Mission, as well as already published specimens from earlier archaeological research. It has been noted to date that this motif is one of the most common on lamps found in Marina el-Alamein. Shells also appear on architectural elements – in the finials of niches with a religious purpose, located in the main reception halls of houses. In such aediculae they are well exposed, but the use of shells does not arise from the shape of the architectural framing. Therefore, other reasons, possibly symbolic ones, for including this motif in decoration should be considered.